Molecular underpinnings of enzalutamide resistance. Issue 11 (November 2018) - Prekovic, S; Van den Broeck, T; Linder, S; van Royen, M E; Houtsmuller, A B; Handle, F; Joniau, S; Zwart, W; Claessens, F
Abstract : Prostate cancer (PCa) is among the most common adult malignancies, and the second leading cause of cancer-related death in men. As PCa is hormone dependent, blockade of the androgen receptor (AR) signaling is an effective therapeutic strategy for men with advanced metastatic disease. The discovery of enzalutamide, a compound that effectively blocks the AR axis and its clinical application has led to a significant improvement in survival time. However, the effect of enzalutamide is not permanent, and resistance to treatment ultimately leads to development of lethal disease, for which there currently is no cure. This review will focus on the molecular underpinnings of enzalutamide resistance, bridging the gap between the preclinical and clinical research on novel therapeutic strategies for combating this lethal stage of prostate cancer.